A Single Arabidopsis Gene Encodes Two Differentially Targeted Geranylgeranyl Diphosphate Synthase Isoforms . Issue 3 (5th October 2016) - Ruiz-Sola, M. Águila; Barja, M. Victoria; Manzano, David; Llorente, Briardo; Schipper, Bert; Beekwilder, Jules; Rodriguez-Concepcion, Manuel
Abstract : GGPP synthase activity essential for chloroplast function and embryo development is provided by two differentially targeted enzyme isoforms encoded by the same gene in Arabidopsis. Abstract: A wide diversity of isoprenoids is produced in different plant compartments. Most groups of isoprenoids synthesized in plastids, and some produced elsewhere in the plant cell derive from geranylgeranyl diphosphate (GGPP) synthesized by GGPP synthase (GGPPS) enzymes. In Arabidopsis ( Arabidopsis thaliana ), five genes appear to encode GGPPS isoforms localized in plastids (two), the endoplasmic reticulum (two), and mitochondria (one). However, the loss of function of the plastid-targeted GGPPS11 isoform (referred to as G11) is sufficient to cause lethality. Here, we show that the absence of a strong transcription initiation site in the G11 gene results in the production of transcripts of different lengths. The longer transcripts encode an isoform with a functional plastid import sequence that produces GGPP for the major groups of photosynthesis-related plastidial isoprenoids. However, shorter transcripts are also produced that lack the first translation initiation codon and rely on a second in-frame ATG codon to produce an enzymatically active isoform lacking this N-terminal domain. This short enzyme localizes in the cytosol and is essential for embryo development. Our results confirm that the production of differentially targeted enzyme isoforms from the same gene is a central mechanism to control the biosynthesis of isoprenoid precursors in different plant cell compartments.